2013
DOI: 10.1186/1756-6606-6-21
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of epileptiform activity by two distinct subtypes of extrasynaptic GABAA receptors

Abstract: BackgroundGABAergic deficit is one of the major mechanisms underlying epileptic seizures. Previous studies have mainly focused on alterations of synaptic GABAergic inhibition during epileptogenesis. Recent work suggested that tonic inhibition may also play a role in regulating epileptogenesis, but the underlying mechanism is not well understood.ResultsWe employed molecular and pharmacological tools to investigate the role of tonic inhibition during epileptogenesis both in vitro and in vivo. We overexpressed tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Extrasynaptic GABA A Rs have been suggested to exert a regulatory function during epileptogenesis and could be novel antiepileptic drug targets [13] . Hence, we went on to …”
Section: Membrane Expression Of Extrasynaptic Gaba a Receptors In Hipmentioning
confidence: 99%
See 2 more Smart Citations
“…Extrasynaptic GABA A Rs have been suggested to exert a regulatory function during epileptogenesis and could be novel antiepileptic drug targets [13] . Hence, we went on to …”
Section: Membrane Expression Of Extrasynaptic Gaba a Receptors In Hipmentioning
confidence: 99%
“…Extrasynaptic GABA A Rs are not sensitive to most of the benzodiazepines; however, they are highly sensitive to 4,5,6,7-tetra-hydroisoxazolo [5,4-c] pyridine-3-ol (THIP) [5,9] . The role of synaptic GABAR-mediated phasic inhibition in epileptogenesis has been well investigated [10,11] , yet recent research efforts have also revealed that extrasynaptic GABA A R-mediated tonic inhibition plays an equivalent or even more critical role in the regulation of epilepsy [12,13] . Moreover, clinical studies have shown that there is a significant down-regulation of δ-subunitcontaining GABA A Rs in brain samples from patients with temporal lobe epilepsy [14] , and that mutation of the δ-subunit is one of the pathogenic mechanisms of epilepsy [15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…significantly increased the tonic current in cultured hippocampal neurons (41). Interestingly, we found that after overexpressing ␣5␤3␥2 receptors, the frequency of mIPSCs was reduced significantly compared with non-transfected controls (Fig.…”
Section: Down-regulation Of Phasic Inhibition Is Not Caused By the Pomentioning
confidence: 65%
“…The overexpression of the ␣5 subunit may displace some ␣1 subunit and, hence, decrease synaptic GABAergic inhibition. Our recent work demonstrated that overexpression of both the ␣6␤3␦ and ␣5␤3␥2 receptors significantly inhibited the formation of epileptiform activity in hippocampal neurons (41). This work suggests that synaptic GABA inhibition is actually reduced after enhancing tonic inhibition.…”
Section: Discussionmentioning
confidence: 88%